Capital Inflows to Emerging Economies - Policy Lessons from the Baltic Boom-Bust cycle 2004-2010 - Berg,Johan; Bonthron,Fredrik (2011)
This study investigates the effects and policy lessons from the surge of capital inflows that the Baltic countries experienced during the period 2004-2008. We discuss the main risks and policy challenges involved with such an episode and assess what scope there was for policy makers to face these challenges. We also devote some attention to the area of measuring exchange rate pressure by application of the EMP index. Our main findings are that the Baltic countries were very limited in their policy options due to their lack of an independent monetary policy. Furthermore it seems as if it would have been very hard for them to take sufficient precautionary measures in time to avoid a deep recession following the global financial crisis, as this extreme event had a large impact all around the world. There was however some scope for better policies within the management of government finances and financial regulation. Regarding the measurement of exchange rate pressure we find that a new approach suggested by Klaassen & Jager (2011) seems to be valid from both an intuitive and practical perspective.
Keywords: Capital Inflows; Baltics; Exchange Market Pressure; Emerging market policies; Financial Stability